2021
DOI: 10.1186/s13643-021-01595-8
|View full text |Cite
|
Sign up to set email alerts
|

A mapping of facilitators and barriers to evidence-based management in health systems: a scoping review study

Abstract: Background Healthcare settings are complex, and the decision-making process is usually complicated, too. Precise use of best evidence from different sources for increasing the desired outcomes is the result of EBM. Therefore, this study aimed to map the potential facilitators and barriers to EBM in health systems to help the healthcare managers to better implement EBM in their organizations. Methods The present study was a scoping review (SR) condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
0
11
0
5
Order By: Relevance
“…Na dimensão "Conteúdo da Mudança", consideramos as atitudes dos participantes perante a gestão da mudança, como positivas, tendo em conta a evidência consultada, (23)(24)(25) que mapeia a confiança, pessoal e interpessoal, a consciencialização e reconhecimento da necessidade para a mudança, os valores e expetativas, como determinantes facilitadores da gestão da mudança.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Na dimensão "Conteúdo da Mudança", consideramos as atitudes dos participantes perante a gestão da mudança, como positivas, tendo em conta a evidência consultada, (23)(24)(25) que mapeia a confiança, pessoal e interpessoal, a consciencialização e reconhecimento da necessidade para a mudança, os valores e expetativas, como determinantes facilitadores da gestão da mudança.…”
Section: Discussionunclassified
“…A interpretação destes resultados permite destacar atitude favorável dos profissionais face à mudança, considerando a utilização da evidência como um valor organizacional, em oposição a falta de confiança acerca do valor e da qualidade da evidência, ou mesmo a resistência para a mudança, considerados como barreiras para a implementação da evidência. (23) Porém, nas subdimensões da Monitorização, Avaliação e Feedback, percebemos que esta função instrumental da gestão é percebida pelos participantes como neutra, sugerindo uma percepção menos positiva das funções exercidas pelos enfermeiros gestores, o que se configura dificultador, tendo em conta que no âmbito organizacional, a monitorização, avaliação e disseminação dos resultados apresentam-se como componentes cruciais para a utilização de pesquisas na prática dos enfermeiros. (29) A dimensão da Motivação acumulou a segunda pior média, logo atrás da dimensão da Liderança.…”
Section: Discussionunclassified
“…That body of research has also shown that policymakers have always encountered many barriers to EIPM; including a lack of available timely evidence, insufficient skills in retrieving and interpreting evidence and lack of access to evidence (including relationships with the producers of evidence). The established literature on EIPM offers some insights into how EIPM can be increased [ 4 ], such as are having access to research publications; having summaries and synthesis of policy relevant evidence, including policy briefs; [ 5 ] upskilling decision makers to be able to understand and interpret scientific evidence; increasing the level interaction between researchers and policymakers; and having supportive and organizational culture that value the use of evidence [ 6 , 7 ]. The literature has also emphasized the need for developing a stronger bridge between research bodies and policymakers through organizing Knowledge Brokers (KBs)[ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Translating such knowledge can be facilitated when the accessible evidence is high quality, understandable and appropriately disseminated to relevant stakeholder groups [9,10]. Ideally, end-users' evidence needs are already known before any knowledge translation activity begins: a recent survey of social security and insurance medicine professionals in the European Union showed that synthesised evidence based on primary research, as reported in guidelines and systematic reviews, is more often needed for their work than primary study evidence alone [11].…”
Section: Introductionmentioning
confidence: 99%